Absolute bioavailability of evacetrapib in healthy subjects determined by simultaneous administration of oral evacetrapib and intravenous [13C8]‐evacetrapib as a tracer. (7th December 2015) - Cannady, Ellen A.; Aburub, Aktham; Ward, Chris; Hinds, Chris; Czeskis, Boris; Ruterbories, Kenneth; Suico, Jeffrey G.; Royalty, Jane; Ortega, Demetrio; Pack, Brian W.; Begum, Syeda L.; Annes, William F.; et al.
Abstract : This open‐label, single‐period study in healthy subjects estimated evacetrapib absolute bioavailability following simultaneous administration of a 130‐mg evacetrapib oral dose and 4‐h intravenous (IV) infusion of 175 µg [ 13 C8 ]‐evacetrapib as a tracer. Plasma samples collected through 168 h were analyzed for evacetrapib and [ 13 C8 ]‐evacetrapib using high‐performance liquid chromatography/tandem mass spectrometry. Pharmacokinetic parameter estimates following oral and IV doses, including area under the concentration‐time curve (AUC) from zero to infinity (AUC[0‐∞]) and to the last measureable concentration (AUC[0‐tlast ]), were calculated. Bioavailability was calculated as the ratio of least‐squares geometric mean of dose‐normalized AUC (oral : IV) and corresponding 90% confidence interval (CI). Bioavailability of evacetrapib was 44.8% (90% CI: 42.2–47.6%) for AUC(0‐∞) and 44.3% (90% CI: 41.8–46.9%) for AUC(0‐tlast ). Evacetrapib was well tolerated with no reports of clinically significant safety assessment findings. This is among the first studies to estimate absolute bioavailability using simultaneous administration of an unlabeled oral dose with a 13 C‐labeled IV microdose tracer at about 1/1000 th the oral dose, with measurement in the pg/mL range. This approach is beneficial for poorly soluble drugs, does not require additional toxicology studies, does not change oral dose pharmacokinetics, and ultimately gives researchers another tool to evaluate absolute bioavailability. Abstract : This study in healthy subjects estimated absolute bioavailability of evacetrapib following simultaneous administration of a single oral dose of 130 mg evacetrapib and a 4‐h intravenous infusion of 175 µg [ 13 C8 ]‐evacetrapib as a tracer. This is among the first studies to estimate absolute bioavailability using simultaneous administration of an unlabeled oral dose with a 13 C‐labeled IV microdose tracer and measurement in the pg/mL range.